Synthesis and biological activity of fluorinated 7-aryl-2-pyridyl-6,7-dihydro[1,2,4]triazolo[1,5-a][1,3,5]triazin-5-amines. - Dolzhenko, Anton; Tan, B.; Dolzhenko, A.; Chiu, G.; Chui, W. (ELSEVIER, 2008)
In our lead finding program, 12 new fluorinated 7-aryl-2-pyridyl-6,7-dihydro[1,2,4]triazolo[1,5-a][1,3,5]triazin-5-amines were prepared via a practical three-step procedure starting from (iso)nicotinic hydrazides. The fluorine substituted aryl fragment was introduced in the last step through cyclocondensation of N-(3-pyridyl-1,2,4-triazol-5-yl)guanidines and fluoro/trifluoromethyl substituted benzaldehydes. The structures of the compounds were confirmed by 1H and 13C NMR spectral data. The tautomeric preferences for the compounds were established using 2D NOESY experiments. The antiproliferative activity of the synthesized 1,2,4-triazolo[1,5-a][1,3,5]triazines was evaluated against breast, colon and lung cancer cell lines. The highest antiproliferative activity in the series was found for 2-(pyridine-3-yl)-7-(4-trifluoromethylphenyl)-6,7-dihydro[1,2,4]triazolo[1,5-a][1,3,5]triazin-5-amine. The lack of inhibitory activity against bovine dihydrofolate reductase (DHFR) indicated that the antiproliferative activity was realized via other mechanisms.